The Effect Of Interpersonal Conflict And Workload On Work Spirit In The General Secretariat Of Bintan Regency - Hendri Herman; Novi Harmadyastuti; Rio Setiawan; Afdal R. Anwar; Raja Muhammad Syoif (Enrichment : Journal of Management, 2022)
The purpose of this study is basically to determine the effect of interpersonal conflict and workload on morale at the General Affairs Agency of the Regional Secretariat of Bintan Regency. The method used in this research is quantitative method. The sample in this study is the honorary employees at the General Section of the Regional Secretariat of Bintan Regency, as many as 60 respondents. Analysis of the data in this study using regression analysis that previously tested the research instrument and classical assumptions with an error rate of 5%. Based on this study, it can be seen that partially there is a significant influence between interpersonal conflicts on morale and workload also has a significant effect on job satisfaction. Based on the test of the coefficient of determination, it can be seen that the coefficient of determination is 0.691. This means that the independent variables (interpersonal conflict and workload), have an influence percentage of 69.1% while the remaining 30.9% is explained by other variables not included in this study.